Community during the Pandemic and Civil Unrest - Anderson, Ronald E. (Int J Community Wellbeing, 2020)
Beginning with the concept of community, this editorial describes the essence of community as connectedness, sharing and caring. The notion of cultural trauma helps clarify the meaning and impact of the pandemic and concurrent racial unrest. Evidence is offered of sharp decline in community wellbeing from these traumas. As in other major disasters, communities of support have arisen to help neighbors and others who need urgent assistance repairing their lives and their torn social fabric.